CU+ ION EXTRACTION FROM A MODIFIED BERNAS ION SOURCE IN A METAL-ION IMPLANTER - Trịnh, Thị Tú Anh (2023)
An ion implanter, which can serve as a metal-ion supply, has been constructed and performance tested. Copper ions are generated and extracted from a Bernas ion source with a heating crucible that provides feed gases to sustain the plasma. Sable arc plasmas can be sustained in the ion source for a crucible temperature in excess of $350^{°}C$. Stable extraction of the ions is possible for arc Currents less than 0.3 A. Arc currents increase with the induced power of a block cathode and the transverse field in the ion source. $Cu^+$ ions in the extracted beam are separated using a dipole magnet. A $20μA$ $Cu^+$ ion current can be extracted with a 0.2 A arc current. The ion current can support a dose of $10^{16}ions/cm^2$ over an area of $15\;cm^2$ within a few hours.